2020
DOI: 10.1002/path.5509
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diagnostic quality cancer pathology images by generative adversarial networks

Abstract: Deep learning‐based computer vision methods have recently made remarkable breakthroughs in the analysis and classification of cancer pathology images. However, there has been relatively little investigation of the utility of deep neural networks to synthesize medical images. In this study, we evaluated the efficacy of generative adversarial networks to synthesize high‐resolution pathology images of 10 histological types of cancer, including five cancer types from The Cancer Genome Atlas and the five major hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 41 publications
0
57
0
Order By: Relevance
“…In the clinical study, the pathologists answered questions about the histotype, the adequacy of image quality and the question of authenticity (real or synthetic). Levine, Peng et al [4] reported slightly better histotype classification performance for synthetic images over real samples in both datasets. In the pathologists' assessment, the fake images were sharper in both datasets, as they preferred synthetic images over real images in terms of quality for histologic evaluation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the clinical study, the pathologists answered questions about the histotype, the adequacy of image quality and the question of authenticity (real or synthetic). Levine, Peng et al [4] reported slightly better histotype classification performance for synthetic images over real samples in both datasets. In the pathologists' assessment, the fake images were sharper in both datasets, as they preferred synthetic images over real images in terms of quality for histologic evaluation.…”
mentioning
confidence: 99%
“…Levine, Peng et al [4] highlight how generative models can be used in the pathology domain with existing computational resources and digitized datasets to produce large high‐quality images that are indistinguishable from real scans, even for experts. Furthermore, as the generator network has no direct access to the real images, Levine, Peng et al [4] suggest that the application of the generative models in combination with other privacy strategies can reduce the risks of patient privacy being compromised. Also, Levine, Peng et al [4] reported a few common GAN‐related artifacts that were encountered in the study and they presented some examples.…”
mentioning
confidence: 99%
See 3 more Smart Citations